Nomenclatural changes in Brazilian Lycopodiaceae - Øllgaard,Benjamin (2012)
This paper presents new nomenclatural combinations in Brazilian Lycopodiaceae, necessary for an upcoming conspectus of the family: there are 39 new combinations in the genus Phlegmariurus, and one in Pseudolycopodiella. Two taxa, formerly treated as varieties of Lycopodiella alopecuroides, are raised to status of species.